On the incompatibility of object fronting and progressive aspect in Yucatec Maya - Uth, Melanie; Gutiérrez-Bravo, Rodrigo; Fliessbach, Jan (Frontiers in Language Sciences, 2024)
In this paper, we present data from an elicitation study and a corpus study that support the observation that the Yucatec Maya progressive aspect auxiliary táan is replaced by the habitual auxiliary k in sentences with contrastively focused fronted objects. Focus has been extensively studied in Yucatec, yet the incompatibility of object fronting and progressive aspect in Yucatec Maya remains understudied. Both our experimental results and our corpus study point in the direction that this incompatibility may very well be categorical. Theoretically, we take a progressive reading to be derived from an imperfectivity operator in combination with a singular operator, and we propose that this singular operator implicates the negation of event plurality, leading to an exhaustive interpretation which ranks below corrective focus on a contrastive focus scale. This means that, in a sentence with object focus fronting, the use of the marked auxiliary táan (as opposed to the more general k) would trigger two contrastive foci, which would be an unlikely and probably dispreferred speech act.